Virtual boardroom - Mbweku, Peter (Midlands State University, 2016)
The purpose of this research was to come up with a solution to problems that were faced at National Railways of Zimbabwe Contributory Pension Fund in conducting their board meetings and other general meetings at large. The organization was failing to comprehend the problems with the current system, hence there was need for a practical solution to do away with the problems at hand. Through the use of interviews, document reviews, questionnaires and observations all the Fund’s problems were identified together with possible solutions to the problems. After having identified the current problems, the following tools were used in the development of the new system, Adobe Dreamweaver CS6, Adobe Photoshop CS6, code igniter framework, MySQL Database. The main objective of the system was to reduce excess amount of money purchasing stationary, overtime payment to employees preparing for board meetings as well as reducing the amount of labour typing, binding and scanning board materials. The planning phase included a detailed feasibility study which aims to find justification for the development of the new system. Results gathered from the feasibility and planning stage were used to design the new system. The system was examined through a series of test procedures so as to remove bugs in the system. With all being done the new Boardpack system was fully implemented and a user manual was produced to help users how to use the system. This dissertation contains five chapters that will walk you from the feasibility stage until the system is fully implemented.